University Rankings
XIV, 274 p.
Keywords: This ground-breaking and exhaustive analysis of university ranking surveys scrutinizes their theoretical bases, methodological issues, societal impact, and policy implications, providing readers with a deep understanding of these controversial comparators. The authors propose that university rankings are misused by policymakers and institutional leaders alike. They assert that these interested parties overlook the highly problematic internal logic of ranking methodologies even as they obsess over the surveys’ assessment of their status. The result is that institutions suffer from short-termism, realigning their resources to maximize their relative rankings. While rankings are widely used in policy and academic discussions, this is the first book to explore the theoretical and methodological issues of ranking itself. It is a welcome contribution to an often highly charged debate. Far from showing how to manipulate the system, this collection of work by key researchers aims to enlighten interested parties. “This is the best book going on university rankings. It provides a reliable, readable, wide-ranging guide for the policy maker, university leader, scholar and would be doctoral student who wants to make sense of the mass of ranking data now available. Shin, Toutkoushian and Teichler tell us how to sort the good, the bad and the ugly in university comparison. A strength of the book, one that guarantees its broad relevance, is the inclusion of contributions from each of the world’s major zones of higher education.” Simon Marginson, Professor, University of Melbourne "This book offers a comprehensive and very timely analysis of a topic of central importance to contemporary higher education: university rankings. Contributors to the book provide a key to the understanding of the theoretical basis and methodological foundations of rankings and their impact on higher education systems and institutions. Illuminating theamazing popularity of rankings, broad and refreshing reflection on the drivers and consequences of rankings are offered.” Jürgen Enders, Professor, University of Twente .